2021
DOI: 10.3390/agronomy11030560
|View full text |Cite
|
Sign up to set email alerts
|

Successive Harvests Modulate the Productive and Physiological Behavior of Three Genovese Pesto Basil Cultivars

Abstract: In the Italian culinary tradition, young and tender leaves of Genovese basil (Ocimum basilicum L.) are used to prepare pesto sauce, a tasty condiment that attracts the interest of the food processing industry. Like other leafy or aromatic vegetables, basil is harvested more than once during the crop cycle to maximize yield. However, the mechanical stress induced by successive cuts can affect crucial parameters associated with pesto processing (leaf/stem ratio, stem diameter, and dry matter). Our research accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 36 publications
(51 reference statements)
3
10
0
Order By: Relevance
“…Variations in yield may result from the interference of environmental factors, such as harvest time, cultural practices, and especially growing conditions that affect primary metabolism. In our study, basil grown in a floating raft system had a significantly higher average fresh yield than that obtained in the open field [ 9 , 26 , 27 ], confirming what Ciriello et al [ 8 , 11 ] observed in three Genovese basil cultivars (Aroma 2, Eleonora, and Italiano Classico). The improved performance recorded in hydroponics could be attributable to unlimited availability of nutrients and water, low abiotic pressure, and high plant densities [ 11 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Variations in yield may result from the interference of environmental factors, such as harvest time, cultural practices, and especially growing conditions that affect primary metabolism. In our study, basil grown in a floating raft system had a significantly higher average fresh yield than that obtained in the open field [ 9 , 26 , 27 ], confirming what Ciriello et al [ 8 , 11 ] observed in three Genovese basil cultivars (Aroma 2, Eleonora, and Italiano Classico). The improved performance recorded in hydroponics could be attributable to unlimited availability of nutrients and water, low abiotic pressure, and high plant densities [ 11 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, the most essential and globally consumed species is Ocimum basilicum L., better known as sweet basil, among which the Genovese type has carved out a prestigious position. Its unique and unmistakable sensory characteristics, conferred by a mixture of monoterpenes and phenylpropanoids, have made it indispensable in traditional Italian dishes (Caprese salad and pizza Margherita) [ 8 , 9 ]. For processing purposes, basil is the crucial ingredient in “pesto sauce”, a renowned green condiment typical of the Liguria region (Italy) that has crossed national borders and become a “must-have” ready-to-eat product of world cuisine [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This might be due to the presence of less competition between basil and tomato when intercropped. In agreement with the present study, Formisano et al (2021) reported that the highest herbal yield in of basil was recorded for both mono-cropping and intercropping with tomato plants. Fresh herb yield was highest for the sole Japanese mint plot, which was statistically on par with intercropping Japanese mint plus one row of onion (Rivest et al 2009;Roshetko et al 2013;Daneshnia et al 2016).…”
Section: Dry Herbal Yield Per Hectaresupporting
confidence: 93%
“…Not least, the reduction in FW recorded in the High Mix versus the High NaCl treatments could be attributable not only to an increase in Cl but also to a decrease in P ( Table 4 ). This element is a limiting factor for plant development as its deficiency leads to a reduction in photosynthesis and the ATP/ADP ratio ( Formisano et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…Basil ( Ocimum basilicum L.) is a native herbaceous plant of southern Asia, also known as the “king of herbs” for its fragrant, delightful, and colorful leaves ( Ciriello et al, 2020 ; Formisano et al, 2021b ). As a culinary herb, it is preferably used fresh to improve the aroma and appearance of salads, pizza, meat, and fish dishes ( Corrado et al, 2020a , b ).…”
Section: Introductionmentioning
confidence: 99%